(untitled) (Al-Qamar, 2021)
Nowadays, human life is facing various threats in all the countries of the world, these threats exist in the form of different types of crimes in different countries. The rate of these crimes is high in some places and less in some places, but the crimes still exist and if they are not stopped, the number of these crimes will increase in the future. Islam has described an excellent and feasible solution for the prevention of these crimes in the form of bounds, which is not only enough to eliminate the evildoers of the society, but also guarantees a peaceful life in the society. To the extent that the Islamic punishment system has existed in Islamic countries, these countries have been protected from various crimes and in countries where the implementation of Islamic punishments has been neglected, the rate of crime has increased every day. Nowadays, there has been a clear relaxation in the enforcement of boundaries in the United Arab Emirates, and Saudi Arabia is also ready to adopt innovation and relax the boundaries in the future. How was the situation? How are the current conditions? And if the bounds are implemented, what will the effects be? And similarly, if other nations adopt the Islamic boundary system, to what extent will they benefit from it? This research article is being written to discuss this in detail.